Dissecting small cell carcinoma of the esophagus ecosystem by single-cell transcriptomic analysis - Hao-Xiang Wu; Yu-Kun Chen; Ying-Nan Wang; Jia-Ying Chen; Shu-Jing Xiang; Ying Jin; Zi-Xian Wang; Chun-Yu Huang; Lu-Ping Yang; Ye He; Wen-Long Guan; Long Bai; et al. (Molecular Cancer)
Abstract Small cell carcinoma of the esophagus (SCCE) is an aggressive and rare neuroendocrine malignancy with poor prognosis. Here, we firstly performed single-cell transcriptional profiling derived from 10 SCCE patients, with normal esophageal mucosa, adjacent non-malignant tissue and tumors from esophageal squamous cell carcinoma (ESCC) as reference. We observed enrichment of activated regulatory T cells and an angiogenesis-induced niche existed in SCCE compared with ESCC, revealing an immune suppressive and vessel-induced tumor microenvironment (TME) in SCCE. Totally, we identified five TME ecotypes (EC1 ~ 5). Notably, EC1 was highly enriched in SCCE, associating with molecular subtyping and survival outcomes. To dissecting heterogeneity of epithelium in SCCE, we constructed eight transcriptional metaprograms (MPs) that underscored significant heterogeneity of SCCE. High expression of MP5 was linked to neuroendocrine phenotype and poor clinical survival. Collectively, these results, for the first time, systematically deciphered the TME and epithelial heterogeneity of SCCE and provided evidences that SCCE patients might benefit from anti-angiogenesis therapy.